Evaluation of water services in Cubijies parish, Chimborazo Province, Ecuador - Sánchez-Moreano, Eliana Soraya; Heredia-Moyano, Sandra Fabiola; Gavilanes-Montoya, Alex Vinicio (Dominio de las Ciencias, 2021)
Water services in Cubijíes parish were evaluated base on stakeholders or users knowledge. The methodology included the identification and the social evaluation; the water services were identified through the consultation to principal actors of the parish, to subsequently evaluate the potential of aquatic ecosystems and vegetable coverage in the provision of water services by means of descriptive statistic. In addition, the existence of factors that modify perception of the capacity of studied ecosystems were determined using non-parametric tests. As a result, the interaction between proposed ecosystems in the provision of water services was recognized, aquatic forest had a predominant role in the supplying of provisioning services; also the factors which changed the perception of the capacity of ecosystems were: level of education, gender and community, social factors had the highest incidence in the scores issued by beneficiaries. It is concluded that water resource has a notorious incidence within the local economy and welfare, therefore inhabitants recognize the existence and importance of water services and related them to the proposed ecosystems.